Effect of GGBFS on Workability and Strength of Alkali-activated Geopolymer Concrete - Gautam Kumar; S. S. Mishra (Salehan Institute of Higher Education, 2021)
This paper focuses on the development of a concrete material by utilizing fly ash and blast furnace slag in conjunction with coarse and fine aggregates with an aim to reduce pollution and eliminate the use of energy extensive binding material like cement. Alternative binding materials have been tried with an aim to get rather an improved concrete material. Alkali-Activated Solution (AAS) made of the hydroxide and silicate solutions of sodium was adopted as the liquid binder whereas, Class F” fly ash and Ground Granulated Blast Furnace Slag (GGBFS) mixed in dry state were used as the Geopolymer Solid Binder (GSB). The liquid binder was used to synthesize the solid binder by thermal curing. The paper investigates the use, influence and relative quantities of the liquid and solid binders in the development of the alkali-activated GGBFS based Geopolymer Concrete (GPC). Varying ratios of AAS to GSB were taken to assess their optimum content. Further, different percentages of GGBFS were used as a partial replacement of Class F fly ash to determine the optimum replacement of GGBFS in the GPC. In order to assess their effects on various properties test samples of cubes, cylinders and beams were cast and tested at 3, 7, and 28 days. Thermal curing of GPC has also resorted for favorable results. It was found that AAS to GSB ratio of 0.5 and GGBFS content of 80% yielded the maximum strength with a little unfavorable effect on workability. The overall results indicated that AAS and GGBFS offer good geopolymer concrete which will find its applicability in water scarce areas. Doi: 10.28991/cej-2021-03091708 Full Text: PDF